2010
DOI: 10.1099/mic.0.028365-0
|View full text |Cite
|
Sign up to set email alerts
|

The novel polysaccharide deacetylase homologue Pdi contributes to virulence of the aquatic pathogen Streptococcus iniae

Abstract: The aquatic zoonotic pathogen Streptococcus iniae represents a threat to the worldwide aquaculture industry and poses a risk to humans who handle raw fish. Because little is known about the mechanisms of S. iniae pathogenesis or virulence factors, we established a highthroughput system combining whole-genome pyrosequencing and transposon mutagenesis that allowed us to identify virulence proteins, including Pdi, the polysaccharide deacetylase of S. iniae, that we describe here. Using bioinformatics tools, we id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
44
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 55 publications
3
44
1
Order By: Relevance
“…Therefore, exposure to blood is likely to occur during human listeriosis, where L. monocytogenes causes meningitis, abortion in pregnant women, and sepsis (11). The results of this and other studies suggest that the role of lysozyme in vivo is multifactorial (9,10,12,50,67) but that serum lysozyme is the major factor that protects against lysozyme-sensitive L. monocytogenes during i.v. infection.…”
Section: Figmentioning
confidence: 58%
See 1 more Smart Citation
“…Therefore, exposure to blood is likely to occur during human listeriosis, where L. monocytogenes causes meningitis, abortion in pregnant women, and sepsis (11). The results of this and other studies suggest that the role of lysozyme in vivo is multifactorial (9,10,12,50,67) but that serum lysozyme is the major factor that protects against lysozyme-sensitive L. monocytogenes during i.v. infection.…”
Section: Figmentioning
confidence: 58%
“…S5A in the supplemental material). We next reasoned that the major bactericidal factor could be macrophages, neutrophils, or serum, since all have been previously implicated in the killing of lysozyme-sensitive bacteria (9,50,51). Upon the infection of bone marrow-derived macrophages, only a small defect was observed when the pgdA oatA pbpX triple mutant, the most lysozyme-sensitive strain, was used (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Staphylococcus aureus and Enterococcus faecalis both utilize O-acetyltransferases to acetylate the C6-OH group of MurNAc (4,19,27). Bacillus cereus, Bacillus anthracis, and several Streptococcus species encode PG deacetylases which remove the acetyl group from GlcNAc, which leads to increased lysozyme resistance (16,31,34,43).…”
mentioning
confidence: 99%
“…Staphylococcus aureus and Enterococcus faecalis both utilize O-acetyltransferases to acetylate the C6-OH group of MurNAc (4,19,27). Bacillus cereus, Bacillus anthracis, and several Streptococcus species encode PG deacetylases which remove the acetyl group from GlcNAc, which leads to increased lysozyme resistance (16,31,34,43).In B. subtilis, several studies have identified genes which are regulated by V ; however, the signal(s) which induces V activity has not been identified (3, 47). We had previously found that only lysozyme was capable of inducing the expression of a sigV homolog, csfV, in Clostridium difficile (20).…”
mentioning
confidence: 99%
“…S. iniae also contains a polysaccharide capsule that functions for protection from phagocytic clearance in whole blood (32,34,39). Furthermore, several genes not previously studied for their virulence traits have been shown to have critical roles during S. iniae infection of hybrid striped bass (HSB), including phosphoglucomutase (pgmA) (8) and a novel polysaccharide deacetylase (pdi) (38).…”
mentioning
confidence: 99%